The ecomuseum as a sustainable product and an accelerator of regional development: The case of the Subcarpathian Province - Katarzyna Negacz; Anna Para (Economic and Environmental Studies (E&ES), 2014)
The purpose of this paper is to assess the influence of ecomuseums on the socio-economic development of the Subcarpathian Province. The research methods include Internet-based survey and literature studies. The paper starts with an overview of the definitions, history and current situation of these museums. The authors examine the influence of ecomuseums on the socio-economic development of the Subcarpathian Province through the list of indicators. The role and function of ecomuseums is investigated in the view of sustainable development principles. Within the past years the concept of sustainable development has been gradually applied within the regional tourism industry in Poland, including the Subcarpathian Province. Sustainable tourism has a positive influence on the region's development and competitiveness. It also involves cooperation among numerous stakeholders and highlights the assets of this province: the quality of the environment alongside with attractive natural and cultural heritage. In the past years the innovative form of an ecomuseum has been introduced in several municipalities. It has had a significant impact on the economic activity of local communities, especially in the mountain areas. Ecomuseum is an innovative model of an open-air museum designed, built, and managed by the local community. It embraces the holistic interpretation of cultural heritage for a sustainable development. More and more ecomuseums are now created around the world.
Keywords: 330; tourism; sustainability; museum